Assessing Competitive Advantages and Challenges of the Ukrainian Tech Ecosystem during Wartime - Lukianenko Iryna H.; Sova Yevgenii S. (Problemi Ekonomiki)
The aim of the article is to identify the competitive advantages and key obstacles hindering the development of the technology sector in Ukraine during the period of martial law, as well as to develop potential scenarios for further development of the innovation ecosystem of Ukraine and appropriate strategies for implementation in each of the scenarios. An additional area of analysis is to test the hypothesis about the key role of investment in stimulating innovation. The study used general statistical and economic approaches, in particular, visual, scenario and correlation analysis. Within the framework of the study, it was demonstrated that the competitive advantages of the innovation ecosystem of Ukraine are a strong research and educational base, a high level of professionalism and technical skills of IT specialists, creativity and a number of innovative technological products. Among the main problems hindering its development are the level of stability of the institutional and regulatory environment, limited access to financial resources and lack of investment. It also confirmed the hypothesis that there is a statistically significant relationship between the level of investment in research and development (R&D) and the number of patents registered. The results of the study can be used to develop appropriate approaches to strategic analysis, in particular in terms of developing scenarios for the development of Ukrainian startups in the face of unprecedented risks, such as the period of martial law. Prospects for further research on this topic are a detailed quantitative and qualitative analysis of the impact of the implementation of programs for financing and stimulating investment in Ukrainian startups on the indicators of innovative development of the technological ecosystem of Ukraine. A separate research task is to develop a road-map for effective institutional changes necessary to ensure a favorable regulatory and business environment for Ukrainian startups based on international experience.